The Importance of a Principal’s Shepherd Leadership in Transforming Teachers' Understanding of the Christian Worldview - Yoel, Jekoniah; Priyatna, Novel (Universitas Pelita Harapan, 2025)
Shepherd leadership is often understood as a form of leadership that takes place within the Church. However, it can also be effectively implemented in other settings, such as schools. In fact, schools may be one of the most ideal environments for shepherd leadership, as they require significant daily interaction among principals, teachers, and students. Shepherd leadership is especially important in schools because a principal cannot achieve the ultimate goals of education alone. It is therefore critical to have teachers who share the school's vision and mission. The purpose of this study is to explore in greater depth how shepherd leadership can transform teachers' understanding of a Christian worldview in their teaching, and how this transformation relates to discipleship in Christ. This research collects data to reveal how shepherd leadership is implemented in the school, how teachers respond to the principal’s leadership, and how their worldviews are transformed as a result.